The Mandala Culture of Anarchy: The Pre-Colonial Southeast Asian International Society - Pandu Utama Manggala (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2013)
Throughout the years, study on pre-colonial Southeast Asian international relations has not garnered major attention because it had long been seen as an integral part of the China-centred tribute system. There is a need to provide greater understanding of the uniqueness of the international system as different regions have different ontologies to comprehend its dynamics and structures. This paper contributes to the pre-colonial Southeast Asian literature by examining the interplay that had existed between pre-colonial Southeast Asian empires and the hierarchical East Asian international society, in particular during the 13th-16th Century. The paper argues that Southeast Asian international relations in pre-colonial time were characterized by complex political structures with the influence of Mandala values. In that structural context, the Majapahit Empire, one of the biggest empires at that time had its own constitutional structures of an international society, albeit still sought close relations with China.